VOCATIONAL ACTIVITY AS A DETERMINANT OF PARTICIPATION IN TOURISM OF DISABLED PEOPLE FROM THE AREA OF EASTERN POLAND - Jarosław Żbikowski; Dominik Dąbrowski; Marek Kuźmicki; Andrzej Soroka (Acta Scientiarum Polonorum. Oeconomia, 2011)
The main purpose of the study, whose results are presented in this paper, was to investigate and assess the influence of the vocational activity on the participation in tourism of people with disabilities residing within the territories of Eastern Poland. The empirical studies using the method of diagnostic survey were conducted in the years 2005–2007 in the following regions: podlaskie, lubelskie and podkarpackie. A comparative analysis of participation in tourism and recreation of two groups of disabled people – vocationally active and inactive – was conducted. There were taken into account the frequency of tourist traveling, preferred forms of tourism, premises and barriers of participation in the activity of tourism and recreation. Studies showed that the vocational activity is an important determinant of participation in tourism of people with disabilities. Conducted studies on the initiative of the Institute of Tourism and Recreation of State School in Biała Podlaska constituted a contribution to studies on the determinants of tourist and leisure activities of disabled people in Poland.